Understanding Communication Research Methods: A Theoretical and Practical Approach, 1st edition - Stephen M, Croucher (Routledge, 2020)
Using an engaging how-to approach that draws from scholarship, real-life, and popular culture, this textbook offers students practical reasons why they should care about research methods and a guide to actually conducting research themselves. Examining quantitative, qualitative, and critical research methods, this new edition helps undergraduate students better grasp the theoretical and practical uses of method by clearly illustrating practical applications. The book features all the main research traditions within communication including online methods, and provides level-appropriate applications of the methods through theoretical and practical examples and exercises, including new sample student papers that demonstrate research methods in action.